1989
DOI: 10.1113/jphysiol.1989.sp017750
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis affects responses of slowly and rapidly adapting airway receptors to pulmonary venous congestion in dogs.

Abstract: SUMMARY1. The effects of plasmapheresis on the responses of rapidly adapting receptors (RARs) and slowly adapting receptors (SARs) of the airways to pulmonary venous congestion were examined in dogs anaesthetized with a-chloralose. Pulmonary venous congestion was produced in a graded manner by partial obstruction of the mitral valve sufficient to raise the mean left atrial pressure by 5, 10 and 15 mmHg. Plasmapheresis was performed by withdrawing 10 % of blood volume twice.2. Both RARs (n = 11) and SARs (n = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…Previous investigations in anaesthetized dogs have shown that manoeuvres designed to increase Qf, i.e. pulmonary venous congestion and a reduction in plasma oncotic pressure, activated the RARs (Kappagoda & Ravi, 1989). Obstruction of the lymphatic drainage from the lung also activated these receptors (Ravi et al 1988).…”
Section: The Starling Forces and Vagal Afferentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations in anaesthetized dogs have shown that manoeuvres designed to increase Qf, i.e. pulmonary venous congestion and a reduction in plasma oncotic pressure, activated the RARs (Kappagoda & Ravi, 1989). Obstruction of the lymphatic drainage from the lung also activated these receptors (Ravi et al 1988).…”
Section: The Starling Forces and Vagal Afferentsmentioning
confidence: 99%
“…The concentration of plasma proteins was reduced by batch plasmapheresis using procedures described previously (Kappagoda & Ravi, 1989). Approximately 10% of the circulating blood volume (estimated in the rabbit as 80 ml kg-') was withdrawn for this purpose.…”
Section: Plasmapheresismentioning
confidence: 99%
See 1 more Smart Citation
“…
We investigated the effects of the substance P (SP) blocker 9]-SP on the response of rapidly adapting pulmonary stretch receptors (RARs) to SP administered into the right atrium, or ammonia vapor inhaled into the lungs in anesthetized, spontaneously breathing rabbits. Right atrial administration of SP (0.3, 1.0, and 3.0/xg/kg) caused an increase in the RAR activity, and this increase became more prominent as the dose of SP was increased.
…”
mentioning
confidence: 99%
“…If so, this may explain the exaggerated respiratory responses to smoke in individuals with heart failure. It has been established that mild pulmonary venous congestion stimulates the pulmonary rapidly adapting receptors (RAR; Kappagoda, Man & Teo, 1987;Kappagoda & Ravi, 1989;Roberts et al 1993). It has also been demonstrated that inhalation of cigarette smoke stimulates the pulmonary vagal sensory receptors, in particular the RAR (Sellick & Widdicombe, 1971;Karlsson, Sant'Ambrogio & Widdicombe, 1988;Kou & Lee, 1990) and the pulmonary C fibre receptors (Lee et at.…”
mentioning
confidence: 99%